The fossil record of birds from the James Ross Basin, West Antarctica - Acosta Hospitaleche, Carolina Ileana Alicia; Jadwiszczak, Piotr; Clarke, Julia A.; Cenizo, Marcos
The fossil record of birds from Antarctica is concentrated in the James Ross Basin, located in north-east of the Antarctic Peninsula. Birds are here represented by an extensive Paleogene record of penguins (Sphenisciformes) and Cretaceous–Paleogene record of Anseriformes, followed by other groups with a minor representation (Procellariiformes, Falconiformes, and Pelagornithidae), and others previously assigned controversially to “Ratites”, Threskiornithidae, Charadriiformes, Gruiformes, Phoenicopteriformes, and Gaviiformes. We provide a complete update of these records, commenting on the importance of some of these remains for the evolution of the major clades. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Jadwiszczak, Piotr. University Of Bialystok; Polonia Fil: Clarke, Julia A. University of Texas at Austin; Estados Unidos Fil: Cenizo, Marcos. Museo de Historia Natural de La Pampa, División Paleontología; Argentina. Fundación de Historia Natural Félix de Azara; Argentina